Effects of caloric restriction on anthropometrical and specific performance in highly trained university judo athletes - Chrara, L.; Raoui, R. A.; Belkadi, A.; Asli, H.; Benbernou, O. (Arab Journal of Nutrition and Exercise, 2018)
Purpose: The purpose of this study was to determine the ultimate body mass, performance, and nutritional characteristics of the Algerian judo junior athletes, and also analysing the impact of nutritional intakes on stabilising Weight loss according to special performance of judo athletes. Material: 21 male university athletes (aged: 21.45 ± 1.32; height: 1.81 ± 0.45 m; and body mass: 73.9 ± 4.1 kg) participated in this study during a period of stabilising weight loss before and after 15 days of caloric restriction. Athletes were submitted to anthropometrical measurements and performed the Special Judo Fitness Test. Values for nutrient intakes were obtained from a 15-day food record kept during a training camp period of weight maintenance and after a 15-day caloric restriction. Results: Caloric restriction resulted in significant decreases in body mass (73.73 ± 2.1) and performance. However, Special Judo Fitness Test index increased significantly (14.00 ± 1.75) during caloric restriction in comparison to stabilising Weight loss. Conclusion: Exercise and caloric restriction lead to determine the ultimate weight and physical performance. The present study provides baseline nutritional data that can be used in the prescription of individual training programs for university judo athletes.